Supervisi Klinis Kepala Sekolah dalam Meningkatkan Kompetensi Pedagogik Guru Sekolah Dasar - Nina Nuraeni; Rifki Firdaus; Suharyanto H. Soro; Ida Tejawiani (Global Education Journal, 2026)
Teacher pedagogical competence is one of the factors that determine the quality of learning in schools. However, the implementation of clinical supervision as an effort to improve this competence has not been fully optimal. This study aims to describe and analyze the clinical supervision of school principals in improving teacher pedagogical competence. The researcher used an approach. Data were collected through observation, interviews, and documentation. The data analysis technique used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that clinical supervision was implemented systematically and referred to teacher needs and academic supervision provisions. The implementation of supervision provided constructive feedback, encouraged teacher reflection, and improved the ability to plan, implement, and evaluate learning. This study concluded that clinical supervision was implemented collaboratively, continuously, and based on teacher needs, contributing to improving teacher pedagogical competence and the quality of learning in schools.